Branching fraction measurement of B+→ωℓ+ν decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We present a measurement of the B+→ωℓ+ν branching fraction based on a sample of 467 million B¯¯¯B pairs recorded by the BABAR detector at the SLAC PEP-II e+e− collider. We observe 1125±131 signal decays, corresponding to a branching fraction of B(B+→ωℓ+ν)=(1.21±0.14±0.08)×10−4, where the first error is statistical and the second is systematic. The dependence of the decay rate on q2, the invariant mass squared of the leptons, is compared to QCD predictions of the form factors based on a quark model and light-cone sum rules.